Treatment of thrice-negative breast cancer in a patient with metabolic syndrome - G. E. Roitberg; J. V. Dorosh; O. Yu. Anikeeva (Исследования и практика в медицине)
Breast cancer (BC) remains one of the most common diseases of the female population. According to statistics, breast cancer is detected in every eighth woman. Approximately 20‑24% of breast cancer patients are diagnosed with triple negative breast cancer. Triple‑negative breast cancer is characterized by an aggressive clinical course, a higher relapse rate, and low overall survival. According to statistics, the median survival rate for women with metastatic triple‑negative breast cancer is less than one year. We demonstrate a successful case of treatment of a 60‑year‑old woman diagnosed with triple negative breast cancer on the right, edematous‑infiltrative form, St IIIC cT4bN3M0 on the background of metabolic syndrome. Antitumor treatment lasted 1 year and consisted of three stages: systemic chemotherapy, surgical treatment (radical mastectomy), and adjuvant radiation therapy. After the treatment, remission was achieved. The patient is alive and has a relapse‑free period of 3 years. Conclusion. Despite the severe concomitant pathology in the observed patient, we received a positive result of multi‑ stage therapy, where cytotoxic chemotherapy was the basic treatment for a woman with triple negative breast cancer.